2011
DOI: 10.3171/2011.1.focus10326
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic biopsy of ventricular tumors: a multicentric experience

Abstract: Object Although neuroendoscopic biopsy is routinely performed, the safety and validity of this procedure has been studied only in small numbers of patients in single-center reports. The Section of Neuroendoscopy of the Italian Neurosurgical Society invited some of its members to review their own experience, gathering a sufficient number of cases for a wide analysis. Methods Retrospective data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 28 publications
(43 reference statements)
1
63
0
Order By: Relevance
“…1C). 7,12,20,21 In the current paper, we present our experience using a combined rigid and flexible endoscopic procedure through a single bur hole for achieving a safer and ideal trajectory for an ETV, as well as an effective method for performing the EBX.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1C). 7,12,20,21 In the current paper, we present our experience using a combined rigid and flexible endoscopic procedure through a single bur hole for achieving a safer and ideal trajectory for an ETV, as well as an effective method for performing the EBX.…”
mentioning
confidence: 99%
“…1B); 3,6,13,14,25,27 and 3) using a flexible endoscope through a single bur hole. 2,[8][9][10]20,23 The limitations of these options are a compromise for both the ETV and for the EBX when using a single bur hole and rigid endoscope, the need for 2 entry points and trajectories in the second option, and compromised visual quality and technical limitations using only a flexible endoscope. To overcome abbreviatioNs EBX = endoscopic biopsy; ETV = endoscopic third ventriculostomy; IVH = intraventricular hemorrhage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendoscopy in the field of neurooncology offers the advantages of improved visualization of intraventricular pathology, better management of tumor-related hydrocephalus, less morbid biopsies, and the allowance of minimally invasive removal of intraventricular tumors. 77,91 Certain characteristics make a tumor ideally suited for endoscopic biopsy or resection. 78 These include moderate to low vascularity, soft-consistency, tumors smaller than 2 cm in diameter, those associated with secondary hydrocephalus, those that are histologically low grade, and lesions situated in the lateral ventricle and pineal region.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…[1][2][3] Endoscopic third ventriculostomy (ETV) is well accepted for obstructive hydrocephalus of various etiologies. [4][5][6][7][8][9][10] It is considered as a better alternative to shunt surgery in obstructive HCP. Though some authors advocate ETV in patients of all ages, [1][2][3]11 others showed that patients younger than 1 year have a higher failure rate for ETVs compared with older children.…”
Section: Introductionmentioning
confidence: 99%